Réponses

2013-12-28T11:05:20+01:00
2013-12-28T11:05:55+01:00
Bonjour

f(x)=(3x+7)²+(18x+42)+(9x²-49)
f(x) = 9x² +42x +49 + 18x +42 + 9x² -49
f(x) = 18x² +60x  +42
Factorisation
f(x) = (3x+7)² + (18x +42) + (3x -7)(3x+7)
(3x+7) (3x+7) + (18x+42 + 3x -7)
(3x+7)(3x+7 + 21x + 35)
(3x+7)(24x +42)
De même pour : 

g(x)=x²+2x+1-(x+1)(2x-7)-(x²-1) 
g(x) = x² +2x +1 -(2x² -7x +2x -7) - (x² -1)
g(x) = x² +2x +1 -2x² +7x -2x +7 - x² +1
g(x) = -2x² +7x +9

factorisation
g(x) = x²+2x+1-(x+1)(2x-7)-(x²-1)
g(x) = (x +1)² - (x+1) (2x-7) - (x-1)(x+1)
g(x) = (x+1)(x+1) - (2x -7) - (x-1)
g(x) = (x+1)(x+1 -2x +7 -x +1)
g(x) = (x+1)( -2x +9)